2012
DOI: 10.1063/1.4731198
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresponse properties of orderly assemblies of BaTiO3 and SrTiO3 nanocube single crystals

Abstract: Orderly assemblies of BaTiO3 (BT) nanocubes, SrTiO3 (ST) nanocubes and BT-ST mixture nanocubes were fabricated on Pt-coated Si substrate directly by solution self-assembly and heated at 850 °C. The dielectric nanocubes aligned face to face in a quite wide region of several tens of square-micrometers with a height of one micrometer, and even inside of the structures was ordered. The piezoresponse of BT-ST mixture assembly showed non-linear curve and stepwise behavior at high poling field, which differed from fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…gel method25 , and also higher than those of BT/ST nanocomposite (59 pm V -1 )45 constructed from BT and ST nanocubes by solution self-assembly and the BT-900 mesocrystal (103 pm V -1 ) prepared in this study. This is due to the perfect orientation matching between the BT and ST nanocrystals in the mesocrystalline BT/ST nanocomposite prepared in this study.…”
mentioning
confidence: 90%
“…gel method25 , and also higher than those of BT/ST nanocomposite (59 pm V -1 )45 constructed from BT and ST nanocubes by solution self-assembly and the BT-900 mesocrystal (103 pm V -1 ) prepared in this study. This is due to the perfect orientation matching between the BT and ST nanocrystals in the mesocrystalline BT/ST nanocomposite prepared in this study.…”
mentioning
confidence: 90%
“…The experimental assembly of BaTiO 3 nanocubes was achieved independently by dip‐coating method and by solvent evaporation . In both cases, the outcome of self‐assembly was a highly ordered mesocrystal structure with simple cubic lattice and long range‐ordering (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Using the oriented anisometric nanoparticles for thin‐film preparation is expected to bring several advantages because they promote crystallization and enhance the orientation of the thin films. In addition, piezoelectric and ferroelectric measurements of the ordered BaTiO 3 —SrTiO 3 nanocubes' assembly revealed that interfacial lattice distortions between the nanocrystallites significantly affect the dielectric and piezoelectric responses . This suggested that the piezoelectric properties could be tuned by the interface‐controlled structures consisting of cubic‐shaped dielectric building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoresponse of the BaTiO3 and SrTiO3 mixture showed a nonlinear curve and stepwise behavior at a high poling field, which differed from ferroelectric BaTiO3 or paraelectric SrTiO3 nanocubes [128].…”
Section: Article In Pressmentioning
confidence: 99%